2016
DOI: 10.1177/1534735416645180
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training for Patients Pre- and Postsurgically Treated for Non–Small Cell Lung Cancer: A Systematic Review and Meta-analysis

Abstract: Background. This meta-analysis examined the effects of exercise training on length of hospital stay, postoperative complications, exercise capacity, 6-minute walking distance (6MWD), and health-related quality of life (HRQoL) in patients following resection of non–small cell lung cancer (NSCLC). Methods. This review searched PubMed, EMBASE, and the Cochrane Collaboration data base up to August 16, 2015. It includes 15 studies comparing exercise endurance and quality of life before versus after exercise trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 38 publications
4
48
0
8
Order By: Relevance
“…During completion of the current review, a new review by Ni et al (13) (evaluating the effects of pre-and post-operative exercise interventions) was published supporting our findings, in contrast their review included all study designs, as well as pre-and post-operative measurements.…”
Section: Strengths and Limitations Of The Review Processmentioning
confidence: 73%
See 1 more Smart Citation
“…During completion of the current review, a new review by Ni et al (13) (evaluating the effects of pre-and post-operative exercise interventions) was published supporting our findings, in contrast their review included all study designs, as well as pre-and post-operative measurements.…”
Section: Strengths and Limitations Of The Review Processmentioning
confidence: 73%
“…In a population diagnosed with myocardial infarction, early-initiated exercise in the acute phase has shown greater benefits on exercise capacity than is the case in exercise interventions initiated in a later treatment phase (11). Systematic reviews investigating the effects of preand post-surgical exercise interventions in patients with NSCLC show that exercise may increase exercise capacity of people following lung resection for NSCLC (6,12,13). However, to date, no systematic reviews have been done investigating the effects of post-surgical exercise interventions for patients with NSCLC focusing on high-quality evidence and only post-operative outcomes to eliminate the impact of the surgery (no pre-operative baseline measurements).…”
mentioning
confidence: 99%
“…Exercise interventions in lung cancer survivors commonly take place as part of comprehensive, multidisciplinary pulmonary rehabilitation programs, either in the preoperative or postoperative context. 37 Recent systematic reviews suggest that preoperative exercise improves cardiopulmonary fitness 38,39 and may reduce the risk of surgical complications, [40][41][42][43] while postoperative exercise may improve functional and/or exercise capacity and QoL. [42][43][44][45] While these findings provide supporting evidence for exercise in lung cancer survivorship, the authors of the systematic reviews raise concerns for volunteer and selection bias and inadequate sample size for the included studies, and note a lack of large randomized controlled trials (RCTs) of exercise interventions for lung cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…37 Recent systematic reviews suggest that preoperative exercise improves cardiopulmonary fitness 38,39 and may reduce the risk of surgical complications, [40][41][42][43] while postoperative exercise may improve functional and/or exercise capacity and QoL. [42][43][44][45] While these findings provide supporting evidence for exercise in lung cancer survivorship, the authors of the systematic reviews raise concerns for volunteer and selection bias and inadequate sample size for the included studies, and note a lack of large randomized controlled trials (RCTs) of exercise interventions for lung cancer survivors. 40,[43][44][45] A more recent RCT 46 examining the impact of physical activity/exercise on fatigue in advanced lung cancer survivors showed no difference compared to usual care; however, in exploratory analyses of 38 (34%) of participants who increased physical activity/exercise during the intervention period, there was a significant reduction in fatigue symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for effectiveness is not as consistent in lung cancer survivors [4]. Recent systematic reviews of exercise interventions in lung cancer survivors suggest that while exercise training can improve functional EC and QoL following curative-intent therapy [24][25][26][27], there are concerns for bias, inadequate sample size, and lack of large randomized controlled trials [24,25,28]. Moreover, a recent systematic review identified numerous patient-related barriers to regular physical activity in lung cancer survivors [29].…”
Section: Discussionmentioning
confidence: 99%